2010
DOI: 10.1007/s11325-010-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

Apnea-hypopnea indices and snoring in children diagnosed with ADHD: a matched case-control study

Abstract: Our PSG findings show no strong link between ADHD and SDB although our findings could be limited by a small sample size. Findings from PSG studies in the literature argue both for and against an association between ADHD and SDB. Our results suggest medication is not a factor in the debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The particular functional importance of sleep-disordered breathing in children with ADHD was shown in a study in which 61 (8–13 year old) children with ADHD with or without obstructive sleep apnea underwent an oddball auditory attention test coupled with detection of P300 (Event related potentials) followed by an all-night PSG, and revealed significant decreased amplitude of the P300 potential in children with Obstructive sleep apnea (OSA) +ADHD, when compared with children with only ADHD (Henriques Filho, 2016). However, there is not complete concordance between studies in this area: a two night PSG data (6–12 years) revealed no significant differences between control group ( n = 28) and children with ADHD ( n = 28) for presence of an AHI >1 (where a threshold of >1 AHI event per hour is of clinical relevance) or snoring (Galland et al, 2011). Further, within the same age group, Prihodova et al (2010) found no significant difference in the occurrence of sleep disordered breathing between ADHD ( n = 31) and control children ( n = 26) following a 2 night PSG and MSLT study.…”
Section: Resultsmentioning
confidence: 97%
“…The particular functional importance of sleep-disordered breathing in children with ADHD was shown in a study in which 61 (8–13 year old) children with ADHD with or without obstructive sleep apnea underwent an oddball auditory attention test coupled with detection of P300 (Event related potentials) followed by an all-night PSG, and revealed significant decreased amplitude of the P300 potential in children with Obstructive sleep apnea (OSA) +ADHD, when compared with children with only ADHD (Henriques Filho, 2016). However, there is not complete concordance between studies in this area: a two night PSG data (6–12 years) revealed no significant differences between control group ( n = 28) and children with ADHD ( n = 28) for presence of an AHI >1 (where a threshold of >1 AHI event per hour is of clinical relevance) or snoring (Galland et al, 2011). Further, within the same age group, Prihodova et al (2010) found no significant difference in the occurrence of sleep disordered breathing between ADHD ( n = 31) and control children ( n = 26) following a 2 night PSG and MSLT study.…”
Section: Resultsmentioning
confidence: 97%
“…This could in part be due to obesity in these patients, probably due to under-registration of overweight in children. It has been claimed that attention deficit hyperactivity disorder is associated with OSA in case series, although carefully controlled trials have failed to find evidence of this 26. This is underlined by our finding that there was no greater incidence of psychiatric disease either before or after an OSA diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…A prospective, case-control study from a psychiatric clinic compared 28 paired children diagnosed with ADHD versus controls [27]. The incidence of SDB was similar in those diagnosed with ADHD and controls; however, frequent snoring occurred at higher frequency in the ADHD group.…”
Section: Cprs (Conners Parent Ratingmentioning
confidence: 99%